2009
DOI: 10.1161/circresaha.108.191460
|View full text |Cite
|
Sign up to set email alerts
|

Myc Regulates Embryonic Vascular Permeability and Remodeling

Abstract: Abstract-Previous work has shown that c-Myc is required for adequate vasculogenesis and angiogenesis. To further investigate the contribution of Myc to these processes, we conditionally expressed c-Myc in embryonic endothelial cells using a tetracycline-regulated system. Endothelial Myc overexpression resulted in severe defects in the embryonic vascular system. Myc-expressing embryos undergo widespread edema formation and multiple hemorrhagic lesions. They die between embryonic days 14.5 and 17.5. The changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…As mentioned above, c-Myc plays a pivotal role in vascular development by promoting VEGFA expression (Baudino et al, 2002; Kokai et al, 2009). In complex with its partner MAX, c-Myc directly binds to classic or nonclassic E-box sequences on DNA (Blackwell et al, 1993; Kim et al, 2008) and recruits histone acetyltransferase to allow chromatin expansion and activate transcription.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, c-Myc plays a pivotal role in vascular development by promoting VEGFA expression (Baudino et al, 2002; Kokai et al, 2009). In complex with its partner MAX, c-Myc directly binds to classic or nonclassic E-box sequences on DNA (Blackwell et al, 1993; Kim et al, 2008) and recruits histone acetyltransferase to allow chromatin expansion and activate transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, these deformities can be partially rescued by transgenic VEGFA expression (Baudino et al, 2002). On the other hand, endothelial-specific c-Myc overexpression in mice also causes embryonic lethality arising from widespread edema, multiple hemorrhagic lesions and severe defects in the vascular network, accompanied by an elevated level of VEGFA (Kokai et al, 2009). Together, these results suggest that the role of c-Myc in vascular development and in promoting VEGFA expression has to be tightly balanced.…”
Section: Introductionmentioning
confidence: 99%
“…Since onco-gene cMyc has been reported to play a role in angiogenesis (Bertl et al, 2006; Kokai et al, 2009), it becomes interesting to see whether cMyc is involved in kaempferol’s regulation on VEGF and whether cMyc is activated by NFκB transcription factor in ovarian cancer cells. Our study found that cMyc is down-regulated by kaempferol treatment concentration-dependently and significantly at both mRNA and protein levels (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…A common link among these genes is their direct or indirect regulation by c-Myc 19 . Previous studies have demonstrated c-Myc’s critical role in angiogenesis during development 9,20,21 and cancer 22,23 , yet its precise role in the heart and individual cellular constituents remains undiscovered despite its gross upregulation and function during cardiac pathology 24,25 . Moreover, most studies have focused on the effect of c-Myc overexpression on angiogenesis, but the consequences of reduced c-Myc levels remain unknown.…”
Section: Introductionmentioning
confidence: 99%